THE EFFECT OF THE SPIRITUAL EMOTIONAL FREEDOM TECHNIQUE (SEFT) ON ANXIETY REDUCTION IN HYDATIDIFORM MOLE PATIENTS - Atun Raudotul Marifah; S. Setyowati; Yati Afiyanti (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2022)
A hydatidiform mole is an abnormal form of pregnancy. Women diagnosed with might face anxiety and lose hope of getting pregnant and having a child. Hydatidiform mole is potentially life-threatening and has the potential to be malignant. One of the treatments for this abnormality is curettage. This study aimed to determine the effect of the Spiritual Emotional Freedom Technique (SEFT) therapy on anxiety reduction in patients with hydatidiform mole. This study reported the intervention trials of SEF therapy to five post-curettage women in a private hospital. The researchers collected the data through observation and questionnaire using Hamilton Anxiety Rating Scale (HARS). The results showed changes in anxiety scores in patients with hydatidiform mole. In conclusion, SEFT therapy was effective in reducing women’s anxiety. Therefore, it is expected that nurses apply SEFT treatment as an alternative nursing intervention to reduce patients’ anxiety.